'Oh I do like to be beside the seaside': opportunity structures for four un/underemployed young people living in English coastal towns. Issue 3 (27th May 2017) - Reid, Hazel; Westergaard, Jane
ABSTRACT: Long-term unemployed young people are a 'social concern' in many countries. The focus for research is usually cities, but may also include rural areas. The qualitative study described in this paper focuses instead on four young people living in coastal towns in South East England. The study suggests that their experiences in education and employment markets are shaped, negatively, by their particular location and the ongoing opportunity structures. The paper outlines their views and discusses the three main themes that emerged from the analysis: opportunity structures, supported resilience and the impact of living in a coastal town. Implications for targeted youth guidance are considered, alongside a consideration of the reflexive role of the researcher in such work.